K-Means Color Segmentation and Morphological Feature Extraction of Bamboo Fiber as an Environmentally Friendly Material for Soil Strengthening - Khoiriya Latifah; Joko Siswanto; Bambang Supriyadi (Universitas Islam Sultan Agung, 2020)
Indonesia is one of the bamboo producing countries. One of the characteristics of good bamboo is that bamboo has a good fiber content as well. Characteristics of a good bamboo fiber is fiber that has a size and length of fiber that is large and long because it will affect the compressive strength and tensile strength of the bamboo. This study uses the K-Means color segmentation method and shape measurements based on the morphological characteristics of bamboo fibers, namely the area, circumference / perimeter and fiber roundness ratio. The results of testing with 18 images of bamboo type training show that Wulung bamboo fiber which is still of the same genus with bamboo Gombong has the largest size fiber of 40.4, the longest perimeter of 3.73 and has a roundness ratio of 0.83 bamboo Ori which has an area of 21, 6, perimeter of 3.23 and a roundness ratio of 0.79. Bambu Petung has an area of 20.6, perimeter of 2.53 and roundness ratio of 0.79. Java Bamboo has an area of 20.2, perimeter of 1.19 and a roundness ratio of 0.8. Whereas Bambu Apus only has an area of 19.2, a perimeter of 2.09 and a roundness ratio of 0.78. Testing using 8 testing images obtained an accuracy rate of 0,625.